2021
DOI: 10.4236/ojmsi.2021.93014
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Modelling of COVID-19 Dynamic in the Context of Madagascar

Abstract: We propose a probabilistic approach to modelling the propagation of the coronavirus disease 2019 in Madagascar, with all its specificities. With the strategy of the Malagasy state, which consists of isolating all suspected cases and hospitalized confirmed case, we get an epidemic model with seven compartments: susceptible (S), Exposed (E), Infected (I), Asymptomatic (A), Hospitalized (H), Cured (C) and Death (D). In addition to the classical deterministic models used in epidemiology, the stochastic model offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The study findings revealed that Markov Chains have a unique steady state distribution regardless of the initial state that is approached by successive iterations from any starting distributions. Other researchers (Din et al, 2020;Kharroubi, 2020;Raherinirina et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…The study findings revealed that Markov Chains have a unique steady state distribution regardless of the initial state that is approached by successive iterations from any starting distributions. Other researchers (Din et al, 2020;Kharroubi, 2020;Raherinirina et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have examined the different factors affecting the spread of covid'19 in a country as in the article by Raherinirina A. et all who modeled the spread of Covid'19 with control variantsRaherinirina et al (2021b) Raherinirina et al (2021a), Malheiro et all published a propagation article with contact restriction Malheiro et al (2020), there are gaps in research on the dynamics of the epidemic, prediction of its future trend taking into account appropriate policies, and the effects of neighbors on the dynamics of covid'19 intensity. Consequently, the aim of this article is to consider spatial neighborhoods in the dynamics of covid'19 in Madagascar's 22 administrative regions.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of R t , or its related counterpart, r, the epidemic growth rate ( Wallinga and Lipsitch, 2007 , Park et al, 2020 ), from available case count data is challenged by limitations or variability in surveillance, uncertainty surrounding the shape of disease parameter distributions, and delays in reporting ( Gostic et al, 2020 ). Despite the enormity of these challenges in the limited surveillance settings common to many lower- and middle-income countries (LMICs), real-time estimation of R t from COVID-19 case-counts has been attempted for most regions of the globe ( $author1$ et al, 7]</id><AuthGrp><Author><in>S.</in><dl> </dl><au>Abbott</au></Author><dl>, </dl><Author><in>J.</in><dl> </dl><au>Hellewell</au></Author><dl>, </dl><Author><in>R.N.</in><dl> </dl><au>Thompson</au></Author><dl>, </dl><Author><in>K.</in><dl> </dl><au>Sherratt</au></Author><dl>, </dl><Author><in>H.P.</in><dl> </dl><au>Gibbs</au></Author><dl>, </dl><Author><in>N.I.</in><dl> </dl><au>Bosse</au></Author><dl>, </dl><Author><in>J.D.</in><dl> </dl><au>Munday</au></Author><dl>, </dl><Author><in>S.</in><dl> </dl><au>Meakin</au></Author><dl>, </dl><Author><in>E.L.</in><dl> </dl><au>Doughty</au></Author><dl>, </dl><Author><in>J.Y.</in><dl> </dl><au>Chun</au></Author><dl>, </dl><Author><in>Y.-W.D.</in><dl> </dl><au>Chan</au></Author><dl>, </dl><Author><in>F.</in><dl> </dl><au>Finger</au></Author><dl>, </dl><Author><in>P.</in><dl> </dl><au>Campbell</au></Author><dl>, </dl><Author><in>A.</in><dl> </dl><au>Endo</au></Author><dl>, </dl><Author><in>C.A.B.</in><dl> </dl><au>Pearson</au></Author><dl>, </dl><Author><in>A.</in><dl> </dl><au>Gimma</au></Author><dl>, </dl><Author><in>T.</in><dl> </dl><au>Russell</au></Author><dl>, </dl><Author><in>C.C.</in><dl> </dl><au>modelling Group</au></Author><dl>, </dl><Author><in>S.</in><dl> </dl><au>Flasche</au></Author><dl>, </dl><Author><in>A.J.</in><dl> </dl><au>Kucharski</au></Author><dl>, </dl><Author><in>R.M.</in><dl> </dl><au>Eggo</au></Author><dl>, </dl><Author><in>S.</in><dl> </dl><au>Funk</au></Author></AuthGrp> ) and has been implemented locally in Madagascar ( Rasambainarivo et al, 2020 , Raherinirina et al, 2021 , Raherinirina et al, 2021 , Narison and Maltezos, 2021 ).…”
Section: Introductionmentioning
confidence: 99%